The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/ani12040408
|View full text |Cite
|
Sign up to set email alerts
|

Sainfoin in the Dams’ Diet as a Source of Proanthocyanidins: Effect on the Growth, Carcass and Meat Quality of Their Suckling Lambs

Abstract: Sainfoin (Onobrychis viciifolia) is a forage legume with a medium content of proanthocyanidins (PAC), which may affect animal performance and product quality. The objective of the present study was to assess the effect of PAC from sainfoin fed to dams, using polyethylene glycol (PEG) as a blocking agent, on the performance and carcass and meat quality of their suckling male lambs. After lambing, twenty lactating dams were fed fresh sainfoin ad libitum plus 200 g per day of barley; ten were orally dosed with wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 42 publications
3
6
0
Order By: Relevance
“…In swine, the 5% grape pomace diet leads to an increase of GPX activity in the colon with respect to the duodenum [52], which was attributed to the presence of the unmetabolised procyanidin trimers. In this trial, the carcass and meat quality of suckling lambs were not affected by the inclusion of CT from sainfoin in the dams' diet [27]. In agreement with previous studies, plasma concentrations of fructosamine in lambs, as indicator of nutritional status [54], were not affected by the presence of CT in the dams' diet.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In swine, the 5% grape pomace diet leads to an increase of GPX activity in the colon with respect to the duodenum [52], which was attributed to the presence of the unmetabolised procyanidin trimers. In this trial, the carcass and meat quality of suckling lambs were not affected by the inclusion of CT from sainfoin in the dams' diet [27]. In agreement with previous studies, plasma concentrations of fructosamine in lambs, as indicator of nutritional status [54], were not affected by the presence of CT in the dams' diet.…”
Section: Discussionsupporting
confidence: 90%
“…The present study is a companion paper to a series of investigations performed in lactating ewes fed with fresh sainfoin during the raising period. According to these studies, sainfoin CT did not negatively affect dam dry matter (DM) intake, milk production, and parasitism [26], nor the growth and carcass and meat characteristics of their suckling lambs [27].…”
Section: Introductionmentioning
confidence: 96%
“…No differences in pH were found depending on the type of animal, in line with several authors [7,23]. The current values are usual for sheep meat [7,[24][25][26], indicating that there was no effect of the pH on the rest of the measured parameters. The values found for the proximal composition agreed with those described by other authors for animals with similar characteristics [7,24,26].…”
Section: Ph and Proximal Compositionsupporting
confidence: 88%
“…Sainfoin is a forage legume with a medium content of proanthocyanidins (PAC), which may affect animal performance and product quality. Therefore, Baila, Lobon, Blanco, Casasus, Ripoll, and Joy [ 13 ] studied the effect of PAC from sainfoin fed to dams, using polyethylene glycol as a blocking agent, on the performance and carcass and meat quality of their suckling male lambs. They found that the presence of PAC in the dams’ diet did not affect the growth, blood metabolites, and carcass weight and fatness of the suckling lambs but decreased the lightness of caudal fat and increased the weight of the digestive compartments.…”
Section: Summary Of Published Papersmentioning
confidence: 99%
“…This Special Issue of Animals , entitled “Carcass and Meat Quality in Ruminants”, aims to compile the recent literature with a focus on carcass development, quality, and valorization in addition to meat quality. It includes ten original research articles about various types of meat from ruminant species (bovine [ 7 , 8 , 9 , 10 , 11 ], ovine [ 12 , 13 , 14 ], and caprine [ 15 , 16 ]) as well as one review article about strategies to reduce E. Coli contamination [ 17 ]. These articles, while their aims are different, provide a deep insight on the current topics of carcass and meat science of ruminants.…”
Section: Introductionmentioning
confidence: 99%